Performance analysis of Real Time PPP for transit of Mercury - Erdogan, B.; Karlitepe, F.; Ocalan, T.; Tunalioglu, N. (ELSEVIER SCI LTD, 2018)
In recent years, Precise Point Positioning (PPP) techniques, which are alternative to relative positioning techniques, have begun to be widely used in Global Navigation Satellite System (GNSS) positioning applications. The PPP technique offers an effective solution to obtain coordinates at high accuracy with a single receiver. Real-time PPP (RT-PPP) solutions can also be provided with real-time correction data and products (ephemerides, satellite clock, bias, etc.) provided by different organizations (International GNSS Service (IGS), European Reference Frame (EUREF), Bundesamt fur Kartographie und Geodasie (BKG), European Space Agency (ESA), German Research Centre for Geosciences (GFZ), etc.). In this regard, RT-PPP applications are getting widespread day by day. Considering this situation in this study, the positional accuracy of RT-PPP was analyzed during the transit of Mercury which was determined to be about 7 h on May 9th, 2016. Two GNSS stations, POVE and BUCU that are in the global IGS network, were chosen. The RT-PPP solutions were performed with BKG Ntrip Client (BNC v2.11.2) software. In the analysis, RTCM3EPH as the broadcast ephemeris stream and CLK10 as the combined orbit/clock product of IGS were used. The results of the RT-PPP solutions were compared with the results of the Post-Process (PP) solutions of the 24-hour data of the same day by using the web-based online AUSPOS service. According to the results, it can be concluded that the positioning accuracies for the RT-PPP approach at the different phases of the transit of Mercury have different characters.
Keywords: Global Positioning System (GPS); Precise Point Positioning (PPP); Real Time PPP (RT-PPP); Transit of Mercury; Accuracy; GPS; BEIDOU; NOISE; Engineering; Instruments & Instrumentation